Análise do dano muscular, força e assimetria na recuperação do treino de kung fu - Barros, Gilvandro Oliveira (2018)
Introduction: Martial art is an activity practiced for millennia and in recent years is growing in Brazil, due to the media's own publicity regarding the positive results in relation to the physical and mental health gain in its practitioners. Among the different types of martial arts we have Kung Fu and his Eagle Claw style in the traditional training situation and post-workout recovery Objective: To analyze the active recovery, with the cryotherapy, evaluating the muscular damage, peak of torque and fatigue in Kung Fu practitioners. Methods: The study sample consisted of 16 males, aged between 18 and 39 years old, graduated with training time of at least 1 year continuous and with experience in competition in this year of practice. All were submitted to the traditional training simulations, but only 8 of the 16 individuals were submitted to the cryotherapeutic treatment with the immersion in ice water, the simulations were carried out at an appropriate training site and the body recovery in a 2000 liter capacity pool. Venous blood collection was performed for the analysis of muscle damage indicators, before, after, 24 and 48 hours after the training, as well as the collection of thermographic images for thermal asymmetric skin temperature analysis. Results: The results presented on muscle power in the lower limbs showed a significant difference after the cold water recovery method in relation to the damage, with squat jump 48h after and the Counter Moviment Jump after 24h and 48h. Regarding muscle damage, the LDH and AST indicators showed a significant improvement after 24 hours in cryotherapy. In the thermography, the asymmetry demonstrated the skin temperature comparing individuals submitted to recovery treatment and those who did not, and the active group had the best results 24h and 48h after. Conclusion: The cryotherapy method promotes improvement in the power in the lower limbs reducing muscle damage mainly after 24 hours serving as an alternative procedure in the recovery and prevention of injuries in Kung Fu practitioners.